Pengaruh Intensitas Penggunaan Media Sosial Terhadap Kesehatan Mental Remaja - Tria Adelia; Icha Delia (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
This study aims to examine the influence of social media usage intensity on adolescents’ mental health in the digital era. Social media has become an essential part of teenagers’ lives as a means of communication, entertainment, and self-expression. However, excessive use can have negative impacts on psychological balance. This research employs a qualitative descriptive method through literature study, analyzing various journals, books, and relevant academic sources. The findings show that the higher the intensity of social media use, the greater the risk of mental health issues such as stress, anxiety, and depression. Conversely, wise and productive use can provide positive benefits, including increased self-confidence and social support. Therefore, maintaining balance in social media usage, along with the active roles of families and schools, is crucial for preserving adolescents’ mental well-being in the digital age.